Low Occurrence of Tuberculosis Drug Resistance among Pulmonary Tuberculosis Patients from an Urban Setting, with a Long-Running DOTS Program in Zambia. (20th June 2010) - Mulenga, Chanda; Chonde, Allan; Bwalya, Innocent C.; Kapata, Nathan; Kakungu-Simpungwe, Mathilda; Docx, Sven; Fissette, Krista; Shamputa, Isdore Chola; Portaels, Françoise; Rigouts, Leen
Abstract : We set out to determine the levels of Mycobacterium tuberculosis resistance to first- and second-line TB drugs in an urban population in Zambia. Sputum samples were collected consecutively from all smear-positive, new and previously treated patients, from four diagnostic centres in Ndola between January and July 2006. Drug susceptibility testing was performed using the proportion method against four first- and two second-line TB drugs. Results . Among 156 new cases, any resistance was observed to be 7.7%, monoresistance to isoniazid and rifampicin was 4.5% and 1.3%, respectively. Of 31 retreatment cases, any resistance was observed to be 16.1%, monoresistance to isoniazid and rifampicin was 3.3% for each drug, and one case of resistance to both isoniazid and rifampicin (multidrug resistance) was detected. No resistance to kanamycin or ofloxacin was detected. Conclusion . Although not representative of the country, these results show low levels of drug resistance in a community with a long-standing DOTS experience. Resource constrained countries may reduce TB drug resistance by implementing community-based strategies that enhance treatment completion.